The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/etc.392
|View full text |Cite
|
Sign up to set email alerts
|

Phytochelatin induction by selenate in Chlorella vulgaris, and regulation of effect by sulfate levels

Abstract: Phytochelatins (PCs) are short metal detoxification peptides made from the sulfur-rich molecule glutathione. The production of PCs by algae caused by Se exposure has never been studied, although many algae accumulate Se, forming Se-rich proteins and peptides, and higher plants have demonstrated PC production when treated with Se; therefore, a goal of the current study was to examine whether Se induces PC production in algae. Furthermore, selenate is thought to compete with sulfate in the S assimilation pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Based on PSII fluorescence, oxygen evolution, and pigment production data, it can be concluded that 40 mg·L −1 of selenate was a sublethal concentration for Chlorella sorokiniana culture and can therefore be used for SeMet accumulation studies. Similar findings for Chlorella vulgaris were reported in which chlorophyll production was not significantly affected by exposure to selenate during 9 days of batch cultivation [9]. …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Based on PSII fluorescence, oxygen evolution, and pigment production data, it can be concluded that 40 mg·L −1 of selenate was a sublethal concentration for Chlorella sorokiniana culture and can therefore be used for SeMet accumulation studies. Similar findings for Chlorella vulgaris were reported in which chlorophyll production was not significantly affected by exposure to selenate during 9 days of batch cultivation [9]. …”
Section: Resultssupporting
confidence: 88%
“…The primary cause of Se deficiency that reduces growth, reproduction, and even causes death is its low amount in soil and consequently in animal feed [8]. Selenium bioeffects are mainly involved in immune function, reproduction, metal toxicity resistance, and other biological functions [9]. Besides, selenium has been proven to be an effective anticancer agent mainly based on statistical and model studies [10], when it is supplied in a suitable bioactive form [11–13].…”
Section: Introductionmentioning
confidence: 99%
“…15,67 Se could activate PCs synthase, increase the amount of PC precursors, and stimulate plants to produce more PCs that would eventually form more heavy metal-PC complexes. 68 Our recent study found that melatonin increased the GSH content by stimulating the activity of γ-glutamylcysteine 69 and elevated the PC content by activating PC biosynthetic genes, PCS 15 . In agreement with earlier results, we found that Se, Cd, and melatonin increased the levels of GSH and PCs in tomato leaves (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…We found that pcs-1 ( tm1748 ) knockouts were more sensitive than wild-type to selenium, which is a known contaminant of the Mud River. While the relationship between phytochelatin and selenium remains unstudied in nematodes, algae [52] produce phytochelatin upon exposure to selenium, and selenium forms trisulfide linkages with phytochelatin in vitro [38]. The greater sensitivity of pcs-1 ( tm1748 ) knockout nematodes to sodium selenite in comparison to wild-type worms and a corresponding lack of induction of metallothionein expression after exposure to selenium, in concert with research by other groups demonstrating the greater importance of phytochelatin in comparison to metallothionein in the elimination of metals, suggest that phytochelatin is responsible for mitigating the effects of excess selenium in nematodes.…”
Section: Discussionmentioning
confidence: 99%